A Case of Epidermolysis Bullosa Simplex (Dowling-Meara 1 Type) in Newborn - Gahyun Hong; Minsun Choi (Korean Society of Neonatology, 2022)
Epidermolysis bullosa is a rare genetic skin disease in which skin easily peels off and blisters are formed with mild mechanical trauma. It is classified into simple, borderline, dysmorphic, and mixed type. These four subtypes are further classified according to the location of gene mutation and genetic patterns. Epidermolysis bullosa simplex (EBS) is characterized by separation in the epidermal or subepidermal layer. And it is mostly caused by mutation of keratin 5 (KRT5) and KRT14 genes. Recently, genetic test has become increasingly important for diagnosis, confirming subtypes and genetic counseling. And there are moderate correlation exists between the EBS phenotype and genotype. Here, we report a case of 2-day-old boy with EBS Dowling-Meara type (EBS-DM) diagnosed by mutation analysis in KRT14.